The Analysis of Financial Performance of Tourism Sector Company Listed on the Indonesian Stock Exchange Before and During the COVID-19 Pandemic - Memet Tenan; Kunti Sunaryo; Retno Yulianti (International Journal of Tourism and Hospitality in Asia Pasific, 2024)
This study aims to analyze the financial performance of the hotel, restaurant, and tourism sub-sectors listed on the Indonesia Stock Exchange (IDX) before and during the COVID-19 pandemic. Financial performance is measured by using the ratio of liquidity (CR), solvency, activity (DER), activity ratio (TATO), and profitability (ROA). The data used are secondary data obtained from the official website of IDX in 2018-2021. The population of this study is 38 companies and the number of research samples is 26 companies, which were obtained through purposive sampling in 2018-2021. The analytical method used is descriptive statistical test, data normality test, and Wilcoxon signed rank test. The results of this study show that CR and DER both increased during the pandemic compared to before, while TATO and ROA decreased. The decline in TATO is attributed to inefficient asset allocation, and the lower ROA is due to ongoing operating costs during the pandemic. In summary, there are differences in CR, DER, TATO, and ROA of hotel, restaurant, and tourism subsector companies that are listed on the IDX between before and during the COVID-19 pandemic.